Peran Konseling Keluarga Akibat Tuntutan Kehidupan Modern - Novandry Anggara; Syajaro Tuddur; Sabrina Nurul Aisyah; Hidayani Syam (JURNAL ILMIAH RESEARCH STUDENT, 2025)
Family counseling is a process of providing assistance and guidance to families to help them overcome problems and achieve harmony. Family counseling can help families understand themselves and their surroundings, as well as develop their potential optimally. As a result, families can become stronger and more stable in facing modern life challenges, such as changes in communication patterns, reduced quality time with family, changes in roles and responsibilities, the influence of global culture, and financial challenges. Family counseling can improve effective communication, harmony, and better problem management, enabling families to achieve harmony and stability in facing life challenges. Literature review is a mandatory activity in research, aimed at developing both theoretical and practical aspects. A literature review is a reality that quantitative research uses a scientific approach that combines elements of deductive and inductive reasoning. Family counseling helps families overcome problems and achieve harmony by understanding themselves and their surroundings. The impacts of modern life faced by families include changes in communication patterns, reduced quality time together, changes in roles, the influence of global culture, and financial challenges. Modern family counseling assists families by fostering rational decision-making, training, and mediation.